Religion in Colonial México - Abang, Jasmine A. (The Toro Historical Review, 2020)
The writing of colonial Mexican religious history starts with early 20th-century French historian Robert Ricard and his focus on missionary preaching and teaching endeavors. Ricard, whose historical writing reflects a pre-WWII Eurocentrism and Catholic victory mindset, relied heavily on Spanish and religious sources. In his work, he concludes that the missionary conversion process was successful spiritual conquest. Louise Burkhart's 1989 The Slippery Earth sets a new tone for colonial religious research, claiming that the process of conversion was not one-directional. Burkhart argues that the Nahua of central Mexico had more significance in the development of colonial Mexican Catholicism than Ricard imagined. Burkhart's book becomes the foundation of modern research on the topic, as it is the first to incorporate native-language sources. She heavily utilizes the sixteenth-century Florentine Codex, the twelve-book encyclopedic style manuscript written by Nahua elites under the supervision of Fray Bernardino de Sahagún telling of the culture and the people of Central México. Through her findings, she argues that the Mexican colonial religion reflects a cross-cultural interaction, which ultimately gave birth to what she coins 'Nahuatized Christianity.'